How Picture Storybook Improve Creative Thinking Skills and Learning Outcomes of Elementary School Students? - Darmawan, Lutfi Andi; Wuryandani, Wuri (LPPM Undiksha, 2022)
The lack of creative and innovative media use can make the atmosphere of learning activities tend to be boring and students find it difficult to understand the subject matter discussed in class, so that students become less active, independence and interaction of students in the learning process is not visible so that students tend to be passive and uncommunicative. This study aims to produce an appropriate Picture Storybook, produce the practical picture Storybook, and reveal the effectiveness of the media produced to improve students’ thinking skills and learning outcomes. This research was R&D with the Borg & Gall model. The subjects in this study were fourth-grade elementary school students. Data collection in the initial study was carried out through observation and interviews. Product validation was carried out by material experts and media experts. Data analysis used independent sample t-test and MANOVA test. The results of this study are in the form of a picture storybook that is suitable for use based on the results of the validation with the